Synergistic Effects of Nano-Silicon and IQ Combi on Yield Traits of Wheat under Saline Irrigation - Raghad S. Abbas; Ayyad W. Al-Shahwany; Leila Z. Miandoab; Nader Chaparzadeh (مجلة مركز بحوث التقنيات الاحيائية)
Background: Salinization negatively affects plant growth and development, removing up to 1.5 million hectares of farmland from production annually. Objective: Evaluate the synergistic of Nano-fertilizers on yield traits of wheat Triticum aestivum below saline irrigation. Methodology: two factorial plot experiments were conducted during Autumn 2022 and 2023 in Diyala, IRAQ. The plants were irrigated every 18 days from planting with three NaCl irrigation levels: 0 (distilled water), 50, and 75 mM. A foliar application of nano fertilizer was sprayed after the third leaf appeared every 15 days, three times in total. Results: The salinity significantly decreased the yield component, biological yield, and harvest index, while the synergistic effects of (S), (Q), and (M) increased by 52.86%, 15.81%, and 18.84%   in 2022 and 41.05%, 20.65% and 22.62 in 2023 growth season, respectively. Additionally, the most significant effects of the synergistic nano-fertilizer on catalase, peroxidase, and Proline under salinity were 23.84%, 70.00%, and 79.78% in 2022 and 24.50%, 73.33% and 74.36% in 2023, respectively. Conclusions: The application of nano-fertilizers enhanced yield parameters and increased the antioxidant enzymes as part of the plant's defense mechanism against oxidative stress. Over time, this response to developing salinity-tolerant wheat varieties with strong antioxidant defense systems.